2012
DOI: 10.1111/j.1365-3059.2012.02697.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemicity of Xanthomonas campestris pv. musacearum and time to disease expression after inflorescence infection in East African highland and Pisang Awak bananas in Uganda

Abstract: Banana xanthomonas wilt (XW) caused by Xanthomonas campestris pv. musacearum (Xcm) attacks all banana cultivars. Xcm in inflorescence-infected Pisang Awak plants with wilting male bud bracts is restricted to the upper parts of the true stem; therefore, cutting these plants at the pseudostem base has been recommended to prevent further Xcm spread. In order to fine-tune existing control strategies, this study examined the movement of Xcm into plants and mats, in relation to disease incubation period. Mature Pisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 14 publications
2
75
0
Order By: Relevance
“…An internal cross-section of a floral stalk shows yellow bacterial ooze from the vascular bundles, while a cross section of a fruit shows rusty brown stains in the fruit pulp (Thwaites et al, 2000; Tushemereirwe et al, 2003; Biruma et al, 2007; Ocimati et al, 2013a,b). Late floral symptoms (when the banana bunch is physiologically mature) have also been reported due to tool-mediated infections (Ocimati et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…An internal cross-section of a floral stalk shows yellow bacterial ooze from the vascular bundles, while a cross section of a fruit shows rusty brown stains in the fruit pulp (Thwaites et al, 2000; Tushemereirwe et al, 2003; Biruma et al, 2007; Ocimati et al, 2013a,b). Late floral symptoms (when the banana bunch is physiologically mature) have also been reported due to tool-mediated infections (Ocimati et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…, showed only 3% of suckers sampled from symptomatic mats in farmers' fields (with a 70% plant disease incidence) in eastern DR Congo to test positive for Xcm using Xcm -specific PCR primers. Ocimati et al (2013aOcimati et al ( , 2014 through on station experiments also showed that not all plants in a mat got infected with Xcm when the parent banana plants were artificially inoculated with bacteria through the inflorescence. The observations in the current study do support the findings by .…”
Section: Discussionmentioning
confidence: 99%
“…The cultural practices that include rouging and destroying infected plants/mats, early removal of male buds, disinfection of farm tools and use of clean planting materials are so far the most effective ways of reducing the inoculum in infested fields (Yirgou and Bradbury, 1968;Tushemereirwe et al, 2004). The adoption of rouging and complete destruction of infected mats, early male bud removal and disinfection of farm tools has been poor because they are cumbersome and costly (Jogo et al, 2013;Ocimati et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations